L'Assistance maternelle de Montréal (1912-1961): un exemple de marginalisation des bénévoles dans le domaine des soins aux accouchées - Baillargeon, Denyse (Dynamis, 1999)
Keywords: Assistance maternelle; Femmes

Making Do: Women, Family, and Home in Montreal during the Great Depression - Baillargeon, Denyse (Wilfrid Laurier University Press, 1999)
Translators: _:n32037
Keywords: Crise; Famille; Femmes

La colocation comme situation de communication interculturelle, le discours de cinq jeunes français vivant avec des québécois - Ferrand, Nathalie (Université du Québec à Montréal, 1999)
Keywords: Français; Locataires; Logement

La philanthropie et la violence maritale. Le cas de la Montreal Society for the Protection of Women and Children et de la Woman's Christian Temperance Union of the Province of Quebec - Hébert, Fernand (Université du Québec à Montréal, 1999)
Keywords: Enfants; Famille; Femmes; Philanthropie

Portrait multidimensionnel de la pauvreté sur l'île de Montréal: une étude de la précarité et de la subsistance à partir des données du recensement de la population (1986 et 1996) - Julien, Frédéric (Université de Montréal, 1999)
Keywords: Pauvreté

"This is our Work": The Women's Division of the Canadian Department of Immigration and Colonization, 1919-1938 - Mancuso, Rebecca (Université McGill, 1999)
Anglophone women, working in a new capacity as federal civil servants, exercised a significant influence on Canadian immigration policy in the interwar years. This dissertation focuses on the women's division of the Canadian Department of Immigration and Colonization, an agency charged with recruiting British women for domestic service from 1919 to 1938. The division was a product of the women's wing of the social reform movement and prevailing theories of gender difference and anglo-superiority. Tracing its nearly twenty years of operations shows how the division, initially regarded as a source of imperial strength and a means of English Canada's cultural survival, came to symbolize the disadvantages of Canada's connection to Great Britain and supposed weaknesses inherent in the female character. This institutional study explores the real and imagined connections among gender, imperialism, and the changing socio-economic landscape of interwar Canada. Lien avec Montréal - dans la thèse
Keywords: Femmes; Fonctionnaires

Rethinking Juvenile Prostitution: Insights from Youths on the Street - Morris, Jason (Université McGill, 1999)
Keywords: Enfants; Prostitution

The Homeless, the Whore, the Drunkard, and the Disorderly: Contours of Female Vagrancy in the Montreal Courts, 1810-1842 - Poutanen, Mary Anne (Gendered Pasts: Historical Essays in Femininity and Masculinity in Canada, 1999)
Keywords: Délinquance; Femmes; Itinérance; Prostitution

Étude sur l'évolution d'enfants âgés de 6 à 12 ans et de leur famille suivis par les services externes des centres de réadaptation pour jeunes en difficulté d'adaptation des Centres jeunesse de Montréal - Touchette, Luc (Université de Sherbrooke, 1999)
Keywords: Enfants

La robe montréalaise bourgeoise, 1870-1883: clichés, tendances et contextes de consommation - Vallières, Nicole (Université Laval, 1999)
Keywords: Bourgeoisie; Vêtements

Claims on Housing Space in Nineteenth-Century Montreal - Gilliland, Jason A.; Olson, Sherry (Urban History Review / Revue d'histoire urbaine, 1998)
Number: 2
Keywords: Famille; Logement; Mobilité résidentielle

La promotion de l’hygiène privée: les autorités sanitaires de la province de Québec et la propagande hygiéniste en territoire québécois (1908-1946) - Angers, Daniel (Université de Sherbrooke, 1998)
Keywords: Mortalité; Publicité; Tuberculose

Gouttes de lait et soif de pouvoir: les dessous de la lutte contre la mortalité infantile à Montréal, 1910-1953. - Baillargeon, Denyse (Bulletin canadien d'histoire de la médecine / Canadian Bulletin of Medical History, 1998)
Number: 1
Keywords: Enfants; Goutte de lait; Mortalité

On s’est rencontré simplement… - Baillargeon, Denyse (Cap-aux-Diamants, 1998)
Number: 55
Keywords: Famille; Mariage

Re-Working Respectability: the Feminisation of Clerical Work and the Politics of Public Virtue in Early Twentieth-Century Montreal - Boyer, Kate (Power, Place and Identity: Historical Studies of Social and Legal Regulation in Quebec, 1998)
Keywords: Femmes; Travail

Shadrach Minkins: From Fugitive Slave to Citizen - Collison, Gary (Harvard University Press, 1998)
Keywords: Esclaves; Noirs

The Romance of Reunion: Montreal War Veterans Return to Family Life, 1944-1949 - Fahrni, Magda (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1998)
Number: 1
Keywords: Famille; Guerre

Modeling Residential Mobility in Montreal, 1860-1900 - Gilliland, Jason A. (Historical Methods, 1998)
Number: 1
Keywords: Famille; Logement; Mobilité résidentielle

Différenciation sociale et rituels du mariage: les Montréalais francophones, 1925-1940 - Girard, Denise (Université Laval, 1998)
Keywords: Francophones; Mariage

Tangled Webs: Remarriage and Family Conflict in Nineteenth-Century Quebec - Gossage, Peter (Power, Place and Identity: Historical Studies of Social and Legal Regulation in Quebec, 1998)
Keywords: Famille; Mariage

Le renforcement des normes sur la violence maritale. Le cas de la Montreal Society for the Protection of Women and Children, 1882-1920 - Hébert, Fernand (Bulletin d'histoire politique, 1998)
issued: 1998-24-00
Keywords: Enfants; Famille; Femmes

BURLAND, JEFFREY HALE - Keating, Peter (Dictionnaire biographique du Canada, 1998)

"Pour se créer un avenir". Stratégies de couples montréalais au XIXe siècle - Olson, Sherry (Revue d'histoire de l'Amérique française, 1998)
Number: 3
Keywords: Famille

Manliness, Goodness, and God: Poverty, Gender, and Social Reform in English-Speaking Montreal, 1890-1929 - Perry, Ann Kirsten (Université Queen's, 1998)
Keywords: Anglophones; Pauvreté; Réformistes

Pour une politique de restauration familiale: une analyse du discours de l'école sociale populaire dans le Québec de l'entre-deux-guerres - Quesney, Chantale (Université du Québec à Montréal, 1998)
Keywords: Famille; École Sociale Populaire

Les espaces de pauvreté - Séguin, Anne-Marie (Montréal 2001. Visages et défis d'une métropole, 1998)
Keywords: Pauvreté

Le phénomène des jeunes de la rue à Montréal le cas des Haïtiens - Uwumuremyi, Marie D'Amour (Université du Québec à Montréal, 1998)
Keywords: Haïtiens; Itinérance

« Empêcher la famille »: Fécondité et contraception au Québec, 1920-60 - Gauvreau, Danielle; Gossage, Peter (Canadian Historical Review, 1997)
Number: 3
Keywords: Contraception; Famille; Femmes; Fécondité

Industrial Efficiency, Social Order and Moral Purity: Housing Reform Thought in English Canada, 1900–1950 - Purdy, Sean (Urban History Review / Revue d'histoire urbaine, 1997)
Number: 2
Keywords: Logement; Réformistes

Joe Beef de Montréal - Beaudoin, Léo (Montréal en tête, 1997)
issued: 1997-23-00
Keywords: Alcool; Auberges; McKiernan; Charles dit Joe Beef; Restaurant; Taverne Joe Beef

Cloisonnement ethnique et solidarité captive. Famille Lao dans le quartier Côte-des-Neiges - Bertheleu, Hélène; Billion, Pierre (Le quartier Côte-des-Neiges à Montréal. Les interfaces de la pluriethnicité, 1997)
Keywords: Côte-des-Neiges; Laotiens; Quartiers

Vivre un choc culturel à 65 ans: le cas des personnes âgées haïtiennes en HLM à Montréal - Bontemps, Eva (Université du Québec à Montréal, 1997)
Keywords: Haïtiens; Logement

Class, Culture, Family and the Law: Wife to Widow in Nineteenth-Century Quebec - Bradbury, Bettina (Programme d'études sur le Québec de l'Université McGill, 1997)
Keywords: Femmes; Mariage; Veuvage

Les séparations de corps dans le district judiciaire de Montréal, de 1900 à 1930 - Cliche, Marie-Aimée (Canadian Journal of Law and Society / La Revue Canadienne Droit et Société, 1997)
issued: 1997-21-00
Keywords: Femmes; Mariage

City at War: The Effects of the Second World War on Verdun, Québec - Durflinger, Serge Marc (Université McGill, 1997)
Keywords: Guerre; Quartiers; Verdun

Les contextes écologiques d'incidence de mauvais traitements à l'égard des enfants dans la région de Montréal - Mayer, Micheline (Université de Montréal, 1997)
Keywords: Enfants

La contribution, le rôle et la place des femmes au Service de préparation au mariage de Montréal, 1944-1972 - Pelletier, Anne (Université de Montréal, 1997)
Keywords: Femmes; Mariage

To Indulge their Carnal Appetites: Prostitution in Early Nineteenth-Century Montreal, 1810-1842 - Poutanen, Mary Anne (Université de Montréal, 1997)
Keywords: Police; Prostitution; Tribunaux

Minorités, majorités et les territoires du quotidien - Ulysse, Pierre Joseph; McAll, Christopher (Le quartier Côte-des-Neiges à Montréal. Les interfaces de la pluriethnicité, 1997)
Keywords: Côte-des-Neiges; Quartiers

Fréquenter les Gouttes de lait: l'expérience des mères montréalaises, 1910-1965 - Baillargeon, Denyse (Revue d'histoire de l'Amérique française, 1996)
Number: 1
Keywords: Enfants; Femmes; Goutte de lait; Mortalité

'If You Had no Money, You Had no Trouble, Did You?' Montréal Working-Class Housewives during the Great Depression - Baillargeon, Denyse (Canadian Women. A Reader, 1996)
Keywords: Crise; Famille; Femmes

Les politiques familiales au Québec. Une perspective historique - Baillargeon, Denyse (Lien social et Politiques, 1996)
issued: 1996-23-00
Keywords: Enfants; Famille; Femmes

L'entraide au quotidien: l'exemple de la paroisse Ste-Brigide, Montréal, 1930-1945 - Bonnier, Lucie (Université du Québec à Montréal, 1996)
Keywords: Sainte-Brigide (paroisse)

Un type de maison ouvrière: le déclin de la maison de fond de cour à Montréal, 1880-1920 - Carey, Luc (Université du Québec à Montréal, 1996)
Keywords: Logement

Le bain Généreux: reflet d'un quartier - Écomusée du fier monde (Écomusée du fier monde, 1996)
Keywords: Centre-sud (quartier); Quartiers

A Monograph of Violent Juvenile Crime in Montreal North - Epprecht, Nicola (Université de Montréal, 1996)
Keywords: Criminalité; Enfants

Montréal à l’heure des bains - Labonne, Paul (Continuité, 1996)
issued: 1996-22-00

La mendicité au centre-ville de Montréal: étude du paradoxe du mendiant - Touchette, Daniel (Université du Québec à Montréal, 1996)
Keywords: Itinérance; Pauvreté

City Unique: Montreal days and nights in the 1940s and '50s - Weintraub, William (McClelland & Stewart, 1996)

Familles ouvrières à Montréal. Âge, genre et survie quotidienne pendant la phase d’industrialisation - Bradbury, Bettina (Boréal, 1995)
Keywords: Alimentation; Famille; Logement; Vêtements

Les procès en séparation de corps dans la région de Montréal, 1795-1879 - Cliche, Marie-Aimée (Revue d'histoire de l'Amérique française, 1995)
issued: 1995-22-00
Keywords: Femmes; Mariage

Le choléra de 1832 dans le Bas-Canada: mesure des inégalités devant la mort - Dechêne, Louise; Robert, Jean-Claude (Santé et société au Québec: XIXe-XXe siècle, 1995)
Keywords: Choléra; Mortalité; Épidémies

Le problème de l'alcoolisme au Canada français: discours élitaires et mouvements sociaux - Glaude, Rolland (Université de Sherbrooke, 1995)
Keywords: Alcool; Médecine

Le raz de marée irlandais à Montréal - Olson, Sherry; Thornton, Patricia (Les chemins de la migration en Belgique et au Québec: XVIIe-XXe siècles, 1995)
Keywords: Irlandais

Les pratiques d'intervention dans les centres de jour, de soir et unité mobile pour itinérants de Montréal - Rozier, Marielle (Université du Québec à Montréal, 1995)
Keywords: Itinérance

Les maladies de la misère: Aspects de la santé publique à Montréal 1880-1914 - Tétreault, Martin (Santé et société au Québec: XIXe-XXe siècle, 1995)
Keywords: Alimentation; Enfants; Goutte de lait; Logement; Mortalité; Médecine; Tuberculose; Variole

Rooms of Their Own: The Nurses' Residences at Montreal's Royal Victoria Hospital - Adams, Annmarie (Material History Review / Revue d’histoire de la culture matérielle, 1994)
issued: 1994-23-00
Keywords: Hôpitaux; Infirmières; Logement; Maxwell; Edward; Maxwell; William S.; Royal Victoria Hospital

Care of Mothers and Infants in Montreal Between the Wars: the Visiting Nurses of the Metropolitan Life Milk Deposits and Assistance maternelle - Baillargeon, Denyse (Caring and Curing. Historical Perspectives on Women and healing in Canada, 1994)
Keywords: Assistance maternelle; Enfants; Femmes; Goutte de lait; Infirmières

La mesure alimentaire en milieux défavorisés: a Case Study of the Complex Partnership between Community Groups and Schools to Provide Meals to Schoolchildren in Disadvantaged Areas of Montréal - Beeman, Jennifer (Université du Québec à Montréal, 1994)
Keywords: Alimentation; Enfants; Pauvreté

Women and Technological Change in Nineteenth Century Montreal - Bradbury, Bettina (Women, Work and Place, 1994)
Keywords: Femmes

Working Families: Age, Gender and Daily Survival in Industrializing Montreal - Bradbury, Bettina (Labour / Le travail, 1994)
issued: 1994-21-00
Keywords: Famille; Femmes

Le lesbianisme à Montréal entre 1950 et 1972: une analyse sociologique d'expériences vécues - Chamberland, Line (Université de Montréal, 1994)
Keywords: Femmes

Montréal: habitat et crise de la ville centrale - Choko, Marc H. (ARQ - Architecture Québec, 1994)

Vers un coopératisme social: la Ligue ouvrière catholique et la question du logement dans les années 1940 - Collin, Jean-Pierre (Histoire sociale / Social History, 1994)
Number: 53
Keywords: Ligue ouvrière catholique; Logement

La prostitution féminine à Montréal, 1945-1970 - Lacasse, Danielle (Boréal, 1994)
Keywords: Femmes; Prostitution

Mariages de St-Simon-Apôtre de Montréal, 1953-1991 - Lemieux, Thérèse (Société généalogique canadienne-française, 1994)

Arsène Pigeon, un pionnier du rang d'la Grande-Misère - Prévost, Robert (Mémoires de la Société généalogique canadienne-française, 1994)
issued: 1994-22-00
Keywords: Artisans; Pigeon (famille)

Une place à soi? Aspects du célibat féminin laïc à Montréal à la fin du 19e siècle - Renaud, Catherine (Université de Montréal, 1994)
Keywords: Femmes

Une cité à bâtir: des femmes dans la lutte pour le changement social - Wakeling, Faye (Société, culture et religion à Montréal: XIXe-XXe siècle, 1994)
Keywords: Femmes; Église Unie

Ménagères au temps de la crise - Baillargeon, Denyse (Remue-ménage, 1993)
Keywords: Crise; Famille; Femmes

The Family Economy and Work in an Industrializing City, Montreal in the 1870's - Bradbury, Bettina (Interpreting Canada's Past. Vol. 2: Post-Confederation, 1993)
Keywords: Enfants; Famille; Femmes; Saint-Jacques; Sainte-Anne; Travail

The Fragmented Family: Family Strategies in the Face of Death, Illness and Poverty, Montreal, 1860-1885 - Bradbury, Bettina (Family Patterns, Gender Relations, 1993)
Keywords: Famille; Orphelinats

Working Families: Age, Gender, and Daily Survival in Industrializing Montreal - Bradbury, Bettina (McClelland & Stewart, 1993)
Keywords: Famille; Femmes

Les jeunes de la rue - Côté, Marguerite-Michelle (Liber, 1993)
Keywords: Itinérance

Residential Mobility in Montreal, 1861-1901 - Gilliland, Jason A. (Université McGill, 1993)
Keywords: Famille; Logement; Mobilité résidentielle

Vieillissement et limitations fonctionnelles: analyse comparée des données de l’enquête ESLA entre la région métropolitaine de Montréal et la province de Québec, 1986 - Thouez, Jean-Pierre; Bussière, Yves; Pampalon, Robert; Chicoine, Nathalie (Cahiers québécois de démographie, 1993)
issued: 1993-21-00

Bishop Court Apartments: Symbol of a Lifestyle - Puchalski, Irene (Bulletin | Society for the Study of Architecture in Canada/Société pour l'étude de l'architecture au Canada, 1992)
Number: 3
Keywords: Logement

High Life and Low Life in Edwardian Montreal - McElroy, George E. (The Beaver, 1992)
issued: 1992-02/1992-03

If You Had no Money, You Had no Trouble, Did You?': Montreal Working-Class Housewives During the Great Depression - Baillargeon, Denyse (Women's History Review, 1992)
Number: 2
Keywords: Crise; Famille; Femmes

La crise ordinaire: les ménagères montréalaises durant la crise des années trente - Baillargeon, Denyse (Labour / Le travail, 1992)
issued: 1992-23-00
Keywords: Crise; Famille; Femmes

Ainsi va la ville - Blais, Andrée (Montréal, une histoire à suivre, 1992)
Translators: _:n3353
Keywords: Enseignes; Expositions

City Life - Blais, Andrée (Montreal, a History to Treasure, 1992)
Translators: _:n3464

Gender at Work at Home: Family Decisions, the Labour Market, and Girls' Contributions to the Family Economy - Bradbury, Bettina (Canadian Family History. Selected Readings, 1992)
Keywords: Enfants; Famille; Femmes; Travail

Pigs, Cows and Boarders. Non-wage forms of Survival among Montreal Families, 1861-1881 - Bradbury, Bettina (The Challenge of Modernity: A Reader in Post-Confederation Canada, 1992)
Keywords: Famille; Femmes

Restructuration de la main-d'oeuvre, quartiers multiethniques et équipements collectifs: les pratiques des familles - Chicoine, Nathalie; Germain, Annick (Montréal: tableaux d'un espace en transformation, 1992)
Keywords: Quartiers

La Ligue ouvrière catholique et l'essor du mouvement coopératif d'habitation dans le Québec urbain, au tournant des années 1950 - Collin, Jean-Pierre (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 1992)
issued: 1992-23-00
Keywords: Ligue ouvrière catholique; Logement

Images and Reality of Fatherhood: a Case Study of Montreal's Protestant Middle Class, 1870-1914 - Fish, Cynthia (Université McGill, 1992)
Keywords: Famille; Protestants

Aurore, l'enfant martyre. Essai sur la violence faite aux enfants - Gaudreau, Jean (Sida et santé mentale, 1992)
Number: 1
Keywords: Enfants

Cohabitation et déménagements en milieu ouvrier montréalais: Essai de réinterprétation à partir du cas du village Saint-Augustin (1871-1881) - Lauzon, Gilles (Revue d'histoire de l'Amérique française, 1992)
Number: 1
Keywords: Locataires; Logement; Quartiers; Saint-Augustin

Montréal, métropole du Québec. Images oubliées de la vie quotidienne 1852-1910 - Lessard, Michel (Éditions de l'Homme, 1992)
Keywords: Métropole; Photographie

Familles montréalaises du XIXe siècle: trois cultures, trois trajectoires - Olson, Sherry; Thornton, Patricia (Cahiers québécois de démographie, 1992)
issued: 1992-23-00
Keywords: Anglophones; Famille; Irlandais

Maîtresses de maison dépareillées? L'apprentissage du travail domestique à Montréal au début du siècle - Baillargeon, Denyse (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 1991)
issued: 1991-22-00
Keywords: Enfants; Famille; Femmes

Ménagères au temps de la crise - Baillargeon, Denyse (Remue-ménage, 1991)
Keywords: Crise; Famille; Femmes

'Something Terrible' - Bliss, Michael (The Beaver, 1991)
issued: 1991/1992

Les conditions de vie des femmes: impact du règlement de location en habitation sociale - Brais, Nicole (Université Laval, 1991)
Keywords: Femmes; Locataires; Logement

Les disparités géographiques de la mortalité dans le Montréal métropolitain, 1984-1988: étude écologique des liens avec les conditions sociales, économiques et culturelles - Choinière, Robert (Cahiers québécois de démographie, 1991)
issued: 1991-21-00
Keywords: Mortalité

Les immeubles résidentiels à appartements multiples de type locatif à Montréal, 1889-1914 - Croteau, Danielle (Université du Québec à Montréal, 1991)
Keywords: Logement

Amazons and Victims: Resisting Wife-Abuse in Working-Class Montréal, 1869-1879 - Harvey, Kathryn (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1991)
Number: 1
Keywords: Femmes; Tempérance

To Love, Honour and Obey, Wife-Battering in Working-Class Montreal, 1869-1879 - Harvey, Kathryn (Université de Montréal, 1991)
Keywords: Famille; Femmes

Smoke and Fire: The Chinese in Montreal - Kwok Bun, Chan (The Chinese University Press, 1991)
Keywords: Chinois

La prostitution féminine à Montréal, 1945-1970 - Lacasse, Danielle (Université d'Ottawa, 1991)
Keywords: Femmes; Prostitution

Le marché du travail et les habitudes à risque: la consommation d'alcool - Lambert, Pierre (Université du Québec à Montréal, 1991)
Keywords: Alcool; Travail

To Love, Honour and Obey: Wife-Battering in Working-class Montreal, 1869-1879 - Harvey, Kathryn (Urban History Review / Revue d'histoire urbaine, 1990)
Number: 2
Keywords: Famille; Femmes

Travail domestique et crise économique. Les ménagères montréalaises durant la crise des années trente - Baillargeon, Denyse (Université de Montréal, 1990)
Keywords: Crise; Famille; Femmes

Gender at Work at Home: Family Decisions, the labour Market and Girl's Contributions to the Family Economy - Bradbury, Bettina (Canadian and Australian Labour History. Toward a Comparative Perspective, 1990)
Keywords: Enfants; Famille; Femmes; Travail

The Family Economy and Work in an Industrializing City: Montreal in the 1870s - Bradbury, Bettina (Cities and Urbanization. Canadian Historical Perspectives, 1990)
Keywords: Enfants; Famille; Femmes; Saint-Jacques; Sainte-Anne; Travail

Deviant Anonymous: Single Mothers at the Hôpital de la Miséricorde in Montreal, 1929-1939 - Lévesque, Andrée (Delivering Motherhood: Maternal Ideologies and Practices in the 19th and 20th Centuries, 1990)
Keywords: Femmes; Hôpital de la Miséricorde; Hôpitaux

Montreal of Yesterday: A Snapshot of Jewish Life in Montreal During the Era of Mass Immigration - M. Baker, Zachary (An Everyday Miracle: Yiddish Culture in Montreal, 1990)
Keywords: Juifs; Medres; Israel Jonah

Les conditions de vie et d'études des étudiantes et étudiants de premier cycle à temps complet à l'UQAM - Poirier, Dalida (Université du Québec à Montréal, 1990)
Keywords: Université du Québec à Montréal; Étudiants